Pengaruh Pendidikan Kewirausahaan, Ekspektasi Pendapatan Dan Motivasi Berwirausaha Terhadap Minat Berwirausaha Mahasiswa (Studi Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2020) - Sari, Nabila Aisyara Fatiha; Salim, Muhammad Agus; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to examine and determine the Influence of Entrepreneurship Education, Income Expectations, and Entrepreneurial Motivation on Entrepreneurial Interest of Students (A Study on Students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2020). This research is a quantitative type of research. The method used is multiple linear regression. The sampling technique used the formula from Malhotra with a result of 80 samples. To solve the problems in this study, SPSS assistance was used with validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroskedasticity test, F test, and t test. The research results show that simultaneously the variables of Entrepreneurship Education (X1), Income Expectations (X2), and Entrepreneurial Motivation (X3) have a significant effect on Entrepreneurial Interest (Y). Partial research results show that Entrepreneurship Education (X1), Income Expectations (X2), and Entrepreneurial Motivation (X3) partially have a significant effect on Entrepreneurial Interest (Y). Keywords: Entrepreneurship Education, Income Expectations, Entrepreneurial Motivation